PEMILIHAN JENIS POHON UNTUK KEGIATAN REBOISASI PADA BENDUNGAN WAY APU KABUPATEN BURU - Irwanto, Irwanto; Sahupala, Andjela; Tetelay, Febian Filiph (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
During the construction of the Way Apu Dam, the land was cleared which needed to be rehabilitated. Rehabilitation of this land requires species that can grow well and are also aesthetically pleasing and also have multiple functions. The stages of implementing rehabilitation species selection activities include observation and direct observation, inventory of endemic species in the field, monitoring of species that fail in the field, analysis of problems. Problems with previous planting failures and recommendations for suitable species. The types recommended for rehabilitation of open land are as follows: Samama (Anthocephalus macrophyllus), Pulai (Alstonia scholaris), Mountain Cassowary/Mountain Pine (Casuarina junghuhniana), Eucalyptus (Melaleuca cajuput), Eucalyptus (Eucalyptus alba), Meranti ( Shorea selanica), Lasa (Captanopsis burana), Acacia broadleaf (Acacia mangium), and Sentigi/Papua (Pemphis acidula). Planting on the left and right of the road are: Sentigi/Papua (Pemphis acidula), Mountain Cassowary/Mountain Pine (Casuarina junghuhniana), Samama (Anthocepalus macrophyllus), Pulai (Alstonia scholaris), Lasa (Castanopsis hunta), Meranti (Shorea selanica), Kayu Putih (Melaleuca cajuput), and Acacia broadleaf (Acacia mangium). Selection of species for the area planned for agro-tourism is as follows: Rambutan (Nephelium lappaceum), longan (Dimocarpus longan), types of vegetative mangoes (grafts).